Community Knowledge and Perception on Autopsy in Jatinangor, West Java from August to October 2013 - Siaw Carwen; Berlian Isnia Fitrasanti; Budi Darmawan (Althea Medical Journal, 2015)
Background: Autopsy rate had declined dramatically throughout the world for the past decades. This phenomenon has raised concerns of the medical world. Factors that contributed to this decline include lack of knowledge regarding autopsy among the people, religious reasons, unenthusiastic pathologists and others. This study was conducted to discover the community knowledge and perception of autopsy at Jatinangor, West Java.Methods: A descriptive study was conducted in Jatinangor during the period of August to October 2013. One hundred and ten respondents were included in this study by random sampling. After written informed consent, respondents were given a questionnaire. Collected data were presented in the form of percentages in tables.Results: Most of the respondents were from the age group of 41–50, entrepreneur and senior high school. Eighty seven (79.09%) respondents had heard about the term “autopsy”, but only 66 (75.86%) of them claimed that they knew about autopsy. However, only 53 from 87 respondents (60.92%) truly knew about autopsy. From 110 respondents, 58  (52.72%) of them knew the reasons to perform autopsy. Fifty seven (51.81%) respondents would allow autopsy to be performed on themselves or family members. The main reason was given to discover the exact cause of death. The reasons of  autopsy refusal were afraid of religion concerns and respect for the human body.Conclusions: There are still members of the community who do not know about autopsy and its purposes. It is recommended that the government improves the community knowledge through various activities and programs. DOI: 10.15850/amj.v2n3.522